Knowledge Enhancement of Elementary School Staff about Traumatic Dental Injuries Using Different Educational Tools - Mojtaba Salehi Karizmeh; Fatemeh Mozaffari; Monirsadat Mirzadeh; Razieh Jabbarian (International Journal of Dentistry)
Introduction. This study aimed to assess the efficacy of different educational tools for knowledge enhancement of elementary school staff about the management of traumatic dental injuries (TDIs). Materials and Methods. This quasi-experimental (pretest–posttest) study was conducted on 126 elementary school staff in Qazvin city, who were randomly selected by the cluster sampling in 2020. The baseline knowledge level of the participants about TDIs was assessed by an online questionnaire. Next, they were randomized into the poster, video clip, and no-intervention control groups (56 samples in each group). An informatory poster and a video clip about TDIs were sent to the participants in the first two groups, respectively, through the WhatsApp instant messaging app, and the knowledge level of the three groups was assessed again after 3 weeks. Data were analyzed by ANOVA, McNemar test, chi-square test, and t-test. Results. A significant correlation was noted between the baseline knowledge level of the participants and their educational level, participation in first aid courses covering TDIs, and history of encountering TDIs (P<0.05). The knowledge level of the participants significantly increased after the intervention in the poster and video clip groups (P<0.05). Knowledge enhancement was 43.26% in the poster and 36.61% in the video clip group (P>0.05). Conclusion. Despite the low-baseline knowledge level of the elementary school staff in Qazvin city about TDIs, their knowledge level significantly improved after the educational interventions.